Implementation of real‐time hybrid simulation based on Python‐graphics processing unit computing - Dong, Xiaohui; Tang, Zhenyun; Du, Xiuli (The structural design of tall and special buildings, 2023)
Real‐time hybrid simulation is a testing method that combines physical experiments and numerical simulations, which can increase the dimensions of experimental specimens and reduce the error of scaling testing. Currently, the maximum degrees of freedom of numerical models are 7000 in real time. To improve the scale of numerical simulation in real time, a testing framework based on Python and graphics processing unit was proposed in this paper. The maximum degrees of freedom of the numerical model exceeded 24,000 with the testing framework. The testing capacity of real‐time hybrid simulation was significantly improved by the graphics processing unit calculations.